Early stage Healthcare Technology Assessment - Pecchia, Leandro; Castaldo, Rossano; Melillo, Paolo; Bracale, Umberto; Craven, Michael P.; Bracale, Marcello (Academic Press, 2016)
This chapter presents an overview of HTA methods aiming to inform the research and development of new medical devices, here defined as early stage HTA methods. First, standard HTA methods are briefly introduced and their limits and weaknesses are discussed, with specific regards to medical devices assessment, particularly during research and development phases. Finally, three methods for early stage HTA are introduced: four stages Markov Models, which aims to estimate the cost-effectiveness of new technology when very limited evidence is available; the Headroom, which aims to predict the max reimbursable cost for a medical devices, at least in the best case; the Analytic Hierarchic Process (AHP), which aims to estimate how an innovative healthcare technology meets the main user needs in specific scenarios.